Identification of microorganisms in wet coffee fermentation Coffea arabica Var Catimor and Castillo in Jardín, Antioquia-Colombia, using culture-dependent methods - Motato Rocha, Karina Edith; Gonzalez-Montero, Valentina; Román-Morales , María Orfilia (Vitae, 2024)
Background: Mild Colombian coffees are recognized worldwide for their high-quality coffee cup. However, there have been some failures in post-harvest practices, such as coffee grain fermentation. These failures could occasionally lead to defects and inconsistencies in quality products and economic losses for coffee farmers. In Colombia, one of the fermentation methods most used by coffee growers is wet fermentation, conducted by submerging the de-pulped coffee beans for enough time in water tanks to remove the mucilage. Objectives: We evaluated the effect of the water (g)/de-pulped coffee (g) ratio (I: 0/25, II: 10/25, III: 20/25) and final fermentation time (24, 48, and 72 hours) on the total number of microbial groups. We also identified microorganisms of interest as starter cultures. Methods: We used a completely randomized experimental design with two factors; the effect of the water (g)/de-pulped coffee (g) ratio (I: 0/25, II: 10/25, III: 20/25) and final fermentation time (24, 48, and 72 hours), for 9 treatments with two replicates. During the coffee fermentation (1,950 g), the pH and °Brix were monitored. Total counts of different microbial groups (mesophiles, coliforms, lactic-acid bacteria, acetic-acid bacteria, and yeasts) were performed. Various isolates of microorganisms of interest as starter cultures (lactic-acid bacteria and yeasts) were identified using molecular sequencing techniques. Results: 21 lactic-acid bacteria (LAB) isolates and 22 yeasts were obtained from the different mini-batch fermentation systems. The most abundant lactic-acid bacteria species found were Lactiplantibacillus plantarum (46%) and Levilactobacillus brevis (31%). Pichia kluivery (39%) and Torulaspora delbrueckii (22%) were the most abundant yeast species. Conclusion The studied factors did not have effect over the microorganism’s development. The identified bacterial and yeasts species have potential as starter cultures for better-quality coffees and in fermentation-related applications.